Potensi Kawasan Hutan Mangrove sebagai Kawasan Ecopreneurship di Kota Makassar Indonesia - Khairul, Muh; Arfan, Amal; Sideng, Uca; Chukure, Yosep Immanuel; Al-Jabbar, Ahmad Khairi (UNIVERSITAS NEGERI MAKASSAR, 2023)
The mangrove forest areas in the city of Makassar hold significant potential for sustainable ecopreneurship development. Mangrove forests play a crucial role in preserving coastal ecosystems and offer various economic, social, and environmental benefits. This research aims to analyze the ecopreneurship potential associated with the mangrove forests in Makassar. The research methodology involves field surveys, interviews, and secondary data analysis. The findings reveal that the mangrove forest areas in Makassar have the potential for ecopreneurship development through sustainable endeavors such as eco-tourism, handicraft production, fish farming, and environmental education. Involving local communities, government agencies, and the private sector, the mangrove forest areas can become a source of additional income for local residents while contributing to coastal environmental conservation. Strong collaboration among various stakeholders is necessary to support the ecopreneurship development in the mangrove forest areas of Makassar.AbstrakKawasan hutan mangrove di Kota Makassar memiliki potensi yang besar untuk dikembangkan sebagai kawasan ekopreneurship yang berkelanjutan. Hutan mangrove memiliki peran penting dalam menjaga ekosistem pesisir, serta memberikan berbagai manfaat ekonomi, sosial, dan lingkungan. Penelitian ini bertujuan untuk menganalisis potensi ekopreneurship yang terkait dengan hutan mangrove di Kota Makassar. Metode penelitian melibatkan survei lapangan, wawancara, dan analisis data sekunder. Hasil penelitian menunjukkan bahwa kawasan hutan mangrove di Kota Makassar memiliki potensi untuk dikembangkan sebagai kawasan ekopreneurship melalui berbagai usaha berkelanjutan seperti agrowisata, produksi kerajinan tangan, budidaya ikan, dan edukasi lingkungan. Dengan melibatkan masyarakat lokal, pemerintah, dan sektor swasta, kawasan hutan mangrove dapat menjadi sumber pendapatan tambahan bagi masyarakat setempat dan juga berperan dalam pelestarian lingkungan pesisir. Diperlukan kerja sama yang kuat antara berbagai pihak untuk mendukung pengembangan ekopreneurship di kawasan hutan mangrove Kota Makassar.